Czy miejsce procesu akulturacji rodziców wpływa modyfikująco na poziom rozwoju cech fenotypowych ich potomstwa? - Cieślik, Joachim; Kosińska, Magdalena (Polskie Towarzystwo Antropologiczne, 1993)
DOES THE ORIGIN OF PARENTAL ACCULTURATION INFLUENCE CHILD'S DEVELOPMENT? The purpose of this paper is to analyse the influence of parents' culturgenes on stature and body weight of children distinguished by the origin of parental acculturation.
DOES THE ORIGIN OF PARENTAL ACCULTURATION INFLUENCE CHILD'S DEVELOPMENT?